Phát triển năng lực giải quyết vấn đề toán học cho sinh viên ngành Kinh tế trong dạy học nội dung “Giới hạn của hàm số” (học phần Toán cao cấp) - Lê, Lương Vương; Hoa, Ánh Tường; Nguyễn, Hữu Hậu (Tạp chí Giáo dục, 2026)
In contemporary higher education, the need to innovate teaching methods towards developing learners’ competence is increasingly emphasized. As for students majoring in Economics, the formation and training of mathematical problem-solving competence is the basis for applying knowledge to professional practice. The study proposes a number of measures to develop mathematical problem-solving competence for Economics majors in teaching the content of “Limits of functions” (Advanced Mathematics course). To improve teaching effectiveness through the proposed measures, lecturers need to focus on designing learning activities to enhance students’ experiences and exploration, helping them proactively discover and solve problems; in addition, it is necessary to integrate practical situations related to the economic field into lectures, in order to connect mathematical knowledge with professional contexts.